Sistem Monitoring PKM Berbasis Website Program Studi Informatika FMIPA UNUD (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
From year to year, there are more and more PKM proposals submitted by students in the Informatics Study Program. So far, what has happened is that PKM proposals that enter are sorted manually, namely by students printing their PKM proposals and the proposals will then be distributed to the lecturers in charge of reviewing the proposals. It will take time to evaluate and increase the possibility of repeated errors because the results of the evaluation have no history of recording. Based on these problems, a monitoring system is needed for PKM proposals that enter the Study Program so that later PKM proposals that come in will be more organized and minimize the possibility of errors. The monitoring system is built on a website basis using the laravel framework. Student users can log in and upload PKM proposals, view the results of PKM proposal reviews, revise PKM proposals and update the status of PKM proposals that have been submitted to faculties or universities. Meanwhile, lecturer users can log in and review PKM proposals. After testing with black box testing, the monitoring system has obtained the results as expected.